2007
DOI: 10.1080/13880200701585782
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofHelicteres isora. Bark Extracts on Brain Antioxidant Status and Lipid Peroxidation in Streptozotocin Diabetic Rats

Abstract: The current study investigated the effect of the aqueous extract of Helicteres isora L (Sterculiaceae) bark on oxidative stress in the brains of rats during diabetes. The aqueous extract of H. isora bark was administered orally (100, 200 mg=kg b.w.) and the effect of the extract on blood glucose, plasma insulin, and the levels of thiobarbituric acid reactive substances (TBARS), hydroperoxides, superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione S-transferase (GST), and reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…The presence of many biologically active phytochemicals such as triterpenes, flavonoids, alkaloids, steroids, tannins and glycosides in various plant extracts may be responsible for their respective pharmacological properties (12)(13)(14)(15)(16). Kumar et al,(44) reported that the administration of β-carotene to paracetamol treated rats decreases the elevated activities of serum liver marker enzymes. In the present study, oral administration of both extracts at a concentration of 150 mg/kg b.w daily for 15 days showed a significant hepatoprotecive effect.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of many biologically active phytochemicals such as triterpenes, flavonoids, alkaloids, steroids, tannins and glycosides in various plant extracts may be responsible for their respective pharmacological properties (12)(13)(14)(15)(16). Kumar et al,(44) reported that the administration of β-carotene to paracetamol treated rats decreases the elevated activities of serum liver marker enzymes. In the present study, oral administration of both extracts at a concentration of 150 mg/kg b.w daily for 15 days showed a significant hepatoprotecive effect.…”
Section: Discussionmentioning
confidence: 99%
“…These metabolites offer clues to manufacture new structural types of antimicrobial and antifungal chemicals that are comparatively safe to humans [62]. The classes of secondary metabolites that have greater antimicrobial properties are flavonoids (flavones, flavonols, flavanols, isoflavones, anthocyanidins), phenolic acids (hydroxybenzoic, hydroxycinnamic acids), stilbenes, lignans, quinones, tannins, coumarins (simple coumarins, furanocoumarins, pyranocoumarins), terpenoids (sesquiterpene lactones, diterpenes, triterpenes, polyterpenes), alkaloids, glycosides, saponins, lectins, steroids, and polypeptides [6,16,56,62,[73][74][75][76][77][78][79][80][81][82][83]. These compounds have copious mechanisms that underlie antimicrobial activity, e.g., disturbing microbial membranes, weakening cellular metabolism, control biofilm formation, inhibiting bacterial capsule production, attenuating bacterial virulence by controlling quorum-sensing, and reducing microbial toxin production [3][4][5][6][73][74][75][76][77][78][79][80][81][82][83][84][85].…”
Section: Bioactive Compounds (Bioactive Phytocomponents)mentioning
confidence: 99%
“…Flavonoids are synergistic potentiators with conventional agents in improving the antibiotic efficiency against NTM [194]. Flavonoids generally protect the cells from the harmful effects of ROS generation [198,199]. Markedly, Brynildsen et al [200] suggested that to enhance the antibiotic efficiency not by damaging the bacterial ROS defense systems by flavonoids, but by increasing the endogenous ROS generation in the host, which could negate its capacity to manage with oxidative stress from the available antibiotics.…”
Section: Synergistic Action Of Flavonoids With Antimycobacterial Agentsmentioning
confidence: 99%